Synthesis, structures and photoluminescence properties of mixed ligand divalent metal–organic frameworks. (17th March 2017) - Altaf, Muhammad; Mansha, Muhammad; Sohail, Manzar; Isab, Anvarhusein A.; Ullah, Nisar; Khan, Safyan A.; Sher, Muhammad; Stoeckli-Evans, Helen
Abstract : Crystal engineering is an effective route for synthesis of mixed ligand metal–organic frameworks with attractive topologies and versatile potential applications. Abstract : Three new metal–organic frameworks [Co2 (bmip)(bdc)2 ]·2DMF (1 ), [Cu(bmip)(bdc)]·6H2 O (2 ) and [Zn2 (bmip)(bdc)2 (H2 O)2 ] (3 ) have been prepared using a solvothermal process, derived from a flexible N, N ′-donor spacer 1, 3-bis(2-methylimidazolyl)propane (bmip ) and 1, 4-benzenedicarboxylic acid (H2 bdc ) ligands. Whereas compound1 shows a three-dimensional (3D) framework, exhibiting apcu α-Po network topology, compound2 displays a two-dimensional (2D) network structure lying parallel to the plane (1 1 −1) and shows adia topology. The 2D layers in2 are further linked by hydrogen bonding that involves water solvate molecules, which in turn results in an infinite 3D hydrogen bonded framework. Compound3 on the other hand shows a three-dimensional (3D) complicated framework with zigzag chains having aThSi2 topology. The structural features of1–3 display diverse variations from 3D, 2D and 3D frameworks, respectively, that are entirely different for each transition metal [Co(ii ), Cu(ii ), and Zn(ii )] with the same combination of mixed ligands under similar reaction conditions. The physical and chemical properties of1–3 were investigated by single crystal X-ray diffraction, elemental analysis, FTIR spectroscopy (FTIR), thermogravimetric analysis (TGA) and photoluminescence properties.